Gendered Occupational Interests: Prenatal Androgen Effects on Psychological Orientation to Things Versus People - Beltz, Adriene M. (2011)
There is considerable interest in understanding women’s underrepresentation in science, technology, engineering, and mathematics careers. Career choices have been shown to be driven in part by interests, and gender differences in those interests have generally been considered to result from socialization. We explored the contribution of sex hormones to career-related interests, in particular studying whether prenatal androgens affect interests through psychological orientation to Things versus People. We examined this question in individuals with congenital adrenal hyperplasia (CAH), who have atypical exposure to androgens early in development, and their unaffected siblings (total N = 125 aged 9 to 26 years). Females with CAH had more interest in Things versus People than did unaffected females, and variations among females with CAH reflected variations in their degree of androgen exposure. Results provide strong support for hormonal influences on interest in occupations characterized by working with Things versus People.